EARLY NEOPLASIES OF ESOPHAGUS: IMPROVING OF ENDOSCOPY EXAMINATION IN A NARROW SPECTRUM OF LIGHT - E. V. Peganova (Креативная хирургия и онкология)
In the  article  the  results  of  2650  esophagogastroduodenoscopies of  the  the  high resolution with  NBI (narrow band  imaging) application technology are  presented. In the course  of  research the  author’s  program of  the  automated allocation  of  a pathology of the  esophagus is applied  on  the  basis  of  colour  segmentation of  images.  The authentic improving of NBI endoscopy in diagnosis of the early neoplasies at esophagus is shown. The algorithm of the narrowband endoscopy examination of esophagus, stomach, duodenum with application the automated allocation  of a pathology is also developed.